Analisis Forensik Digital Memori Volatile untuk Mendapatkan Kunci Enkripsi Aplikasi Dm-Crypt - Vipkas Al Hadid Firdaus; Dodit Suprianto; Rini Agustina (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
Disk encryption technology is something very useful in securing data. On the other hand, disk encryption can be used by criminals to hide the digital evidence. The information in the disk will be very useful for the investigation, but if the disk on the computer evidence encrypted then it will hamper the investigation process. The conditions will certainly be a challenge for investigator cybercrime to be able to find the disk encryption key, especially if the perpetrator did not cooperate in the investigation process. The analysis of the image memory to get the encryption key will be helpful in the investigation. In the overall memory activity on the computer evidence will be recorded, using a live image memory dump on the computer evidence, the decryption keys can be recovered. This paper will discuss about forensic analysis to getting the disk encryption key on the dm-crypt is used to encrypt the disk on Linux operating system and prove that through forensic image memory on a live memory dump, key dm-crypt disk encryption can be found with a success percentage of 80%. On this paper the research will be focused on the Linux operating system with dm-crypt function to full disk encryption.